2018
DOI: 10.3892/ijo.2018.4462
|View full text |Cite
|
Sign up to set email alerts
|

High COX-2 expression contributes to a poor prognosis through the inhibition of chemotherapy-induced senescence in nasopharyngeal carcinoma

Abstract: Resistance to radiotherapy and chemotherapy currently represents one of the major reasons for therapeutic failure in nasopharyngeal carcinoma (NPC). However, the mechanisms underlying resistance to chemotherapy in NPC remain unclear. In this study, cell counting assay, cell cycle assay and senescence associated β-galactosidase activity were performed to evaluate cell growth, proliferation and senescence, respectively. We found that the aberrant expression of cyclooxygenase-2 (COX-2) was associated with a poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
(38 reference statements)
0
26
1
Order By: Relevance
“…Our studies and other groups demonstrated that high expression of COX-2 contributes to tumor cell proliferation, metastasis, and drug resistance through regulating several oncogenes or cellcycle-related molecules such as p53, β-catenin, Snail1, etc, in NPC and other cancers. 30,41,42 However, in our study, we found TNF-α, another new molecular positively correlated with COX-2 by RNA-Seq. Bourouba 43 showed that TNF-α promotes tumor growth via a NOS2-dependent mechanism in NPC.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Our studies and other groups demonstrated that high expression of COX-2 contributes to tumor cell proliferation, metastasis, and drug resistance through regulating several oncogenes or cellcycle-related molecules such as p53, β-catenin, Snail1, etc, in NPC and other cancers. 30,41,42 However, in our study, we found TNF-α, another new molecular positively correlated with COX-2 by RNA-Seq. Bourouba 43 showed that TNF-α promotes tumor growth via a NOS2-dependent mechanism in NPC.…”
Section: Discussioncontrasting
confidence: 70%
“…40 Our previous studies showed that a high expression of COX-2 is associated with the recurrence and a poor prognosis of patients with NPC, and COX-2 may play a critical role in chemotherapeutic resistance in NPC via the inhibition of chemotherapy-induced senescence via the inactivation of p53. 30 However, these studies revealed that the COX-2 expression in NPC cells, to the date, there is no report referred to the COX-2 expression of TME in NPC. Several studies revealed that COX-2 promotes tumor metastasis, for example, Zelei reported that COX-2 is highly expressed in NPC cells, which promote the expansion of myeloid-derived suppressor cells with a suppressive function on T cells through inducing the cytokine secretion including IL-6 and GM-CSF.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To confirm the contribution of p53 overexpression to lymphedema, we used a pharmacological approach by testing a known reversible p53 negative modulator, Pifithrin-α (PFT) 44,45 . For this, we set up time mating of Rpl27a low/+ mice with Mdm2 +/or Mdm4 +/mice.…”
Section: Chemical Modulation Of P53 Eliminates Cutaneous Hemorrhagingmentioning
confidence: 99%